2018
DOI: 10.1371/journal.pone.0197587
|View full text |Cite
|
Sign up to set email alerts
|

The association between domestic animal presence and ownership and household drinking water contamination among peri-urban communities of Kisumu, Kenya

Abstract: IntroductionHousehold drinking water can be contaminated by diarrheagenic enteropathogens at numerous points between the source and actual consumption. Interventions to prevent this contamination have focused on preventing exposure to human waste through interventions to improve drinking water, sanitation and hygiene (WASH). In many cases though, the infectious agent may be of zoonotic rather than human origin suggesting that unsafely managed animal waste may contribute to the contamination of household drinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 48 publications
2
37
0
1
Order By: Relevance
“…Similar results regarding the high prevalence of ruminant contamination has been reported for households in rural and urban/peri-urban informal settlements in Bangladesh [12] and Tanzania [10]. In addition, Barnes et al [59] showed an association between domestic animal presence/ownership and household drinking water contamination. Additional work should be done to assess the prevalence of zoonotic pathogens in waters contaminated by ruminant feces and how the persistence of the ruminant target varies relative to pathogen persistence in different environmental media (e.g., water and soil).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Similar results regarding the high prevalence of ruminant contamination has been reported for households in rural and urban/peri-urban informal settlements in Bangladesh [12] and Tanzania [10]. In addition, Barnes et al [59] showed an association between domestic animal presence/ownership and household drinking water contamination. Additional work should be done to assess the prevalence of zoonotic pathogens in waters contaminated by ruminant feces and how the persistence of the ruminant target varies relative to pathogen persistence in different environmental media (e.g., water and soil).…”
Section: Discussionsupporting
confidence: 74%
“…Handwashing with soap is especially critical in preventing food and water contamination [7] by ruminants [60], can reduce diarrheal disease risk by between 40% and 65% [61,62], and can protect against exposure to enteric zoonoses found in animal waste [63]. Although good hand hygiene is particularly protective at certain critical times [59], self-reported handwashing rates in this study population were only 20% before food preparation, 27% before eating, 20% before feeding children, 42% after cleaning children, and 76% after using the toilet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a large portion of the participants in this study reported boiling water prior to use. Unless the water is boiled or treated prior to use each time, stored drinking water can become contaminated at the homesite from domestic animals and vectors, unclean hands and dipping utensils, and the storage container itself (Prüss-Ustün et al 2014;Uddin et al 2014;Ecrumen et al 2017;Barnes et al 2018). Indiscriminate human and animal waste can be a major health hazard in rural Mongolia.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, children and adults especially in the developing countries are suffering from various water-borne diseases [1,2,3]. Problem of providing drinking water guaranteed quality is widely inspread not only for population of peri-urban communities [4,5,6], but also in many regions of Ukraine, especially in the rural settlements of Dnepropetrovsk region [7,8,9,10]. Therefore, in the aspect of legal innovations in the field of preventive medicine the implementation results of sociological survey to the practice of hygienic researches during analyses of the drinking water quality and sanitary conditions of people life is a vital necessity problem.…”
Section: Introductionmentioning
confidence: 99%